The Influence of Tiktok Apps on the Development of Adolescent Social Identity: An Analysis Based on Social Identity Theory - Muhammad Anang Setiadi; Ifadatul Auliah; Galuh Dwinda Salsabillah; Konto Iskandar Dinata (CV. Doki Course and Training, 2026)
This article examines the influence and impact of the TikTok application on the formation of adolescent social identity in a digital context. TikTok, as an increasingly popular platform, provides interactive features for self-exploration, but it also poses challenges such as social comparisons and the pressure to meet expectations. Emerging identities are often temporary and influenced by rapid trends that are analyzed based on social identity theory. The method used is a literature study, collecting and analyzing relevant sources about the influence of TikTok on adolescents' social identity. This research emphasizes the importance of digital education so that adolescents can use social media healthily. These findings provide insight for parents, educators, and policymakers about identity dynamics in the digital age.